Evidências da transferência de energia fluorescente ressonante no sistema ponto quântico - corante através das medidas de microluminêscencia de varredura espacial - Reis, Arnaldo Ferreira dos (2014)
In this work different systems for obtaining a fluorescent resonant energy transfer (FRET) were studied between a donor molecule and the acceptor energy in different modes of operation. For this purpose, we have used a quantum dot (QD) core / shell (CdSe / ZnS) acting as a donor and an organic dye Neutral Red (NR) as the acceptor. FRET is a nonradiative process via dipolar interaction and so that it occurs between a donor and acceptor, certain conditions must be observed as the spectral overlap; choice of appropriate donor and energy acceptor in accordance with the lifetime of both; the appropriate distance between the molecules and the parallel dipole orientation. For the optical characterization of energy transfer mechanism and migration, we have used the following techniques: optical absorption (Ab), photoluminescence (PL) and microluminescence surface scan technique (PL). The study of the photoluminescence spectra in which the donor and acceptor are held in the same platform has shown that the quantum dots undergoes suppression of the dye when there is a lower amount of donor to acceptor, and thus the reduction of the nanocrystal luminescence shows the occurrence of process FRET. Furthermore, in particular, PL technique was applied for analyzing the photon diffusion length (LD) in the same previous samples, and it was observed wider curves when scan curves when the quantity of donors were larger than the acceptor and when a greater dilution of the sample occurs. Thus, this study demonstrated the possibility of obtaining fluorescent resonant nonradiative transfer between quantum dots and dyes in different systems.